2007
DOI: 10.1161/01.atv.0000255311.26383.2f
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Loss of Function Mutation of PCSK9 Gene in White Subjects With Low-Plasma Low-Density Lipoprotein Cholesterol

Abstract: Objectives-The PCSK9 gene, encoding a pro-protein convertase involved in posttranslational degradation of low-density lipoprotein receptor, has emerged as a key regulator of plasma low-density lipoprotein cholesterol. In AfricanAmericans two nonsense mutations resulting in loss of function of PCSK9 are associated with a 30% to 40% reduction of plasma low-density lipoprotein cholesterol. The aim of this study was to assess whether loss of function mutations of PCSK9 were a cause of familial hypobetalipoproteine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 124 publications
(75 citation statements)
references
References 27 publications
2
73
0
Order By: Relevance
“…Rare amino acid changes, p.T77I, p.V114A, p.A522 T, and p.P616L of PCSK9, have been found in hypocholesterolemic blood donors recruited in Sicily (with plasma cholesterol values below the 2nd percentile of the population), and absent in a group of 100 normocholesterolemic controls derived from the general population [Fasano et al, 2007]. Furthermore the threonine, valine, and alanine, at positions 77, 114, and 522, respectively, are conserved among mammalian species and are located in highly-conserved regions of the gene, suggesting that their nonconservative substitution might have some biological effect [Fasano et al, 2007].…”
Section: Biological Relevancementioning
confidence: 97%
See 4 more Smart Citations
“…Rare amino acid changes, p.T77I, p.V114A, p.A522 T, and p.P616L of PCSK9, have been found in hypocholesterolemic blood donors recruited in Sicily (with plasma cholesterol values below the 2nd percentile of the population), and absent in a group of 100 normocholesterolemic controls derived from the general population [Fasano et al, 2007]. Furthermore the threonine, valine, and alanine, at positions 77, 114, and 522, respectively, are conserved among mammalian species and are located in highly-conserved regions of the gene, suggesting that their nonconservative substitution might have some biological effect [Fasano et al, 2007].…”
Section: Biological Relevancementioning
confidence: 97%
“…The p.R46L and p.A443T variants are associated with lower LDL-C levels in population studies [Kotowski et al, 2006;Berge et al, 2006;Fasano et al, 2007;Scartezini et al, 2007]; however, they might be found also in normo-or hypercholesterolemic individuals due to other genetic or environmental factors influencing cholesterol levels [Abifadel et al, 2003;Allard et al, 2005;Kotowski et al, 2006].…”
Section: Biological Relevancementioning
confidence: 99%
See 3 more Smart Citations